Mitophagy in Diabetic Kidney Disease - Zhang, Xiaofeng; Feng, Jing; Li, Xia; Wu, Dan; Wang, Qian; Li, Shuyu; Shi, Changhua (Frontiers in Cell and Developmental Biology, 2021)
Diabetic kidney disease (DKD) is the most common cause of end-stage kidney disease worldwide and is the main microvascular complication of diabetes. The increasing prevalence of diabetes has increased the need for effective treatment of DKD and identification of new therapeutic targets for better clinical management. Mitophagy is a highly conserved process that selectively removes damaged or unnecessary mitochondria via the autophagic machinery. Given the important role of mitophagy in the increased risk of DKD, especially with the recent surge in COVID-19-associated diabetic complications, in this review, we provide compelling evidence for maintaining homeostasis in the glomeruli and tubules and its underlying mechanisms, and offer new insights into potential therapeutic approaches for treatment of DKD.